"Home-wrecking whore": Barnaby Joyce, Vikki Campion, journalism, and the gender politics of the media sex scandal. Issue 7 (2nd October 2020) - Thompson, Jay Daniel
ABSTRACT: This paper addresses journalistic coverage of Australian politician Barnaby Joyce's extramarital relationship with his one time employee, Vikki Campion. The paper suggests that it is productive to examine this coverage as constituting a media sex scandal. Media sex scandals are useful in terms of what they suggest about the gender politics of the society in which they unfold. The Joyce-Campion scandal is revealing because it suggests how the single woman who is involved in a relationship a married man continues to be demonized in a way that the man is not. This, in turn, demonstrates how marriage or rather, a particular, (hetero)sexist model of marriage continues to have a degree of social currency.